The Relationship Between Students’ Habits in Watching English TikTok Content to Their English Grammar Achievement in Vocational High School - Citra Putri Ananda; Cahaya Komara (Universitas Cokroaminoto Palopo, 2024)
TikTok is an application that is widely used. The content on TikTok is not only entertainment but also learning, including learning English. This research set out to investigate whether there is a relationship between students' habits in watching English TikTok content to their English grammar achievement in Vocational High School. The sample and location of this research were 100 students grade 11 at Vocational High School 22 in Jakarta. This research employed a quantitative method with a correlation design. The instruments used in this research were a questionnaire about students' habits in watching English TikTok content and English grammar tests. The research findings indicated that there is a relationship between students' habits in watching English TikTok content to their English grammar achievement in Vocational High School, because a sig value (2-tailed) of 0.000 and where 0.00 < 0.05, then the Pearson correlation value is 0.984, which means students' habits in watching English TikTok content to their English grammar achievement in Vocational High School is very strongly related.